PENGARUH PERCEIVED VALUE TERHADAP TOURIST SATISFACTION: STUDI KASUS BANGKA BELITUNG - Lamia Eva Rini; Rindi Ardika Melsalasa Sahputri; Septiana Sihombing (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
Bangka Belitung Province has strong potential for tourism development, supported by natural beauty and cultural diversity. Increasing revisits is a key indicator of tourism success and regional economic growth. This study aims to examine the influence of perceived value, specifically quality value, emotional value, and social value on tourist satisfaction. Using a quantitative approach and SEM-PLS analysis, data were collected from tourists who visited Bangka Belitung. Results show that emotional value (p = 0.000) and social value(p = 0.032) significantly affect tourist satisfaction, while quality value (p = 0.067) does not. These findings suggest that emotional and social experiences are stronger predictors of satisfaction than perceived service quality. Practical implications recommend destination managers to prioritize emotional engagement and social interaction in experience design. Future studies are encouraged to include additional variables such as e-WOM, destination uniqueness, and tourist demographics to expand the conceptual framework. Keywords: Satisfaction; Perceived Value; emotional value; social value; quality value